PENGARUH CITRA MEREK, KUALITAS LAYANAN, DAN HARGA TERHADAP KEPUASAN PELANGGAN (SURVEI PADA PELANGGAN DISTRIBUTOR CONSUMER GOODS DI TASIKMALAYA) - Mila Karmila; Barin Barlian (Bajang Institute, 2023)
The purpose of this study was to determine and analyze the Effect of Brand Image, Service Quality and Price on Customer Satisfaction either partially or simultaneously on Consumer Goods Distributors in Tasikmalaya City. The object of study was the Consumer Consumer Distributor Distributor in Tasikmalaya City. The research method used is multiple linear regression analysis. Data collection was obtained through observation, questionnaires and literature study. The population in this study was 304 customers. The results showed that Brand Image, Service Quality and Price had a significant effect both partially and simultaneously on customer satisfaction of Consumer Goods Distributors in Tasikmalaya City.